PSNR Improvement using Different Prediction Coding in Image Compression - Khamies K. Hasan (Tikrit Journal of Engineering Sciences, 2010)
Differential Pulse Code Modulation (DPCM) is one of the predictive coding techniques. The number of previous pixels employed in the estimate operation is referred to as the order of the predictor. Predictor using one pixel for estimation is called “first order predictor”. A “second order predictor” utilizes two pixels and an “nth order predictor” would employ n previous pixels. From the results computed in this work, by testing the prediction mean square error (MSE) using different numbers of previous picture elements. The results show that the MSE decreases significantly by using up to three pixels, and further decreases of MSE are rather small by using more than three pixels that means the performance improvement becomes negligible and only a marginal gain beyond a third-order predictor can be achieved. That means, Peak Signal to Noise Ratio (PSNR) increases significantly by increasing the predictor order, the performance improvement becomes negligible beyond third order predictor.